2018
DOI: 10.1016/j.funbio.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and evolution of polyketide biosynthesis gene clusters in the Ceratocystidaceae

Abstract: Polyketides are secondary metabolites with diverse biological activities. Polyketide synthases (PKS) are often encoded from genes clustered in the same genomic region. Functional analyses and genomic studies show that most fungi are capable of producing a repertoire of polyketides. We considered the potential of Ceratocystidaceae for producing polyketides using a comparative genomics approach. Our aims were to identify the putative polyketide biosynthesis gene clusters, to characterize them and predict the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Genome analysis of the fungus Aspergillus oryzae at the beginning of the 21st century revealed that this fungus contains four type III PKS genes (CsyA, CsyB, CsyC, and CsyD), and that other fungi also possess type III PKS genes (Seshime et al, 2005). Since then, type III PKS genes are regularly reported in fungal genomes (for examples, see Lackner et al, 2012;Bertrand et al, 2018;Sayari et al, 2018). Phylogenetic analyses of type III PKSs from plants, bacteria and fungi consistently revealed a unique origin for the fungal clade (Seshime et al, 2005;Goyal et al, 2008Hashimoto et al, 2014Shimizu et al, 2017;Yan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome analysis of the fungus Aspergillus oryzae at the beginning of the 21st century revealed that this fungus contains four type III PKS genes (CsyA, CsyB, CsyC, and CsyD), and that other fungi also possess type III PKS genes (Seshime et al, 2005). Since then, type III PKS genes are regularly reported in fungal genomes (for examples, see Lackner et al, 2012;Bertrand et al, 2018;Sayari et al, 2018). Phylogenetic analyses of type III PKSs from plants, bacteria and fungi consistently revealed a unique origin for the fungal clade (Seshime et al, 2005;Goyal et al, 2008Hashimoto et al, 2014Shimizu et al, 2017;Yan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These findings extend the diversity of starter units fungal type III PKSs can accommodate. In addition to these characterized enzymes, several type III PKS genes have been reported in fungal genomes (Muggia and Grube, 2010;Lackner et al, 2012;Bertrand et al, 2018;Sayari et al, 2018). In other fungi, newly identified SMs are predicted to be synthesized by a type III PKS (Rusman et al, 2018), suggesting that these fungi also contain type III PKS genes.…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have suggested that SMs might play significant roles in the biology of these important fungi [30,31], but such compounds have been only identified in Endoconidiophora resinifera [32]. At the genomic level, the only SM biosynthesis gene clusters characterized in these fungi were those encoding polyketides [33]. The overall goal of this study was therefore to identify and characterize putative NRP biosynthesis clusters and genes in the Ceratocystidaceae .…”
Section: Introductionmentioning
confidence: 99%
“…The glucose oxidase enzymes are intriguing since they convert glucose to hydrogen peroxide (Bankar et al, 2009) and may enable these species to establish their dominance early during the colonization of young flower heads. Glucose is abundant in Protea nectar (Nicolson and Van Wyk, 1998) (Sayari et al, 2018), suggesting that the few secondary metabolite biosynthesis clusters in Knoxdaviesia could be a common trait in Microascalean fungi. These numbers are even lower than the 10 NRPS and PKS genes identified from N. crassa, the model for RIP activity (Galagan et al, 2003).…”
Section: Compounds Mediating Competitionmentioning
confidence: 99%
“…The products synthesized by the remaining nine secondary metabolite clusters in K. capensis and eight in K. proteae are unknown, but may offer protection from predators and other competitors (Brakhage and Schroeckh, 2011). The predicted chalcone and stilbene synthase PKS type-III is also present in the closely related Ceratocystidaceae family (Sayari et al, 2018) and theoretically produces a flavonoid with a role in pigmentation or defence (Austin and Noel, 2003), while the putative geranylgeranyl pyrophosphate synthetase may produce an antimicrobial diterpene or carotenoid (Keller et al, 2005). These secondary metabolite clusters may, therefore, contribute toxic substances that enable Knoxdaviesia to compete in infructescences.…”
Section: Compounds Mediating Competitionmentioning
confidence: 99%